The Application of Experimentation in the Iraqi theatre shows "Othello in the Kitchen" As a model: عادل كريم سالم (Al-Academy, 2016)
The researcher tackles the most outstanding conditions of experimentation, the importance of the study lies in being helpful to the workers in the field of theatre in general and directors in particular which the conditions of experimentation that should be taken.The study aims at knowing the experimental basis which the director (Sami Abdulhamid) followed in the realization of this.The researcher tackles in the First inquiry the concept of experimentation and the second tackles the conditions of experimentation.In the methodology of study the researcher analyzed the show of the "Othello in the Kitchen" and comes up to the following: 1. the dhows has cone with the nature of the previous shows experienced the methods that were not familiar before. The director did not depend on a ready-made directive plan carried by the acting staff because experimentation was concentrated in the play "Othello in the Kitchen" through working on the hypotheses.